Anterior eye shape in emmetropes, low to moderate myopes, and high myopes. Issue 4 (August 2021) - Niyazmand, Hamed; Read, Scott A; Atchison, David A; Collins, Michael J
Abstract: Purpose: Myopia prevalence has increased in recent years, including the levels of high myopia. While myopia has been associated with scleral remodelling and changes in posterior scleral shape, there has been little research examining how myopia affects in-vivo anterior sclera shape. We compared anterior scleral shape in emmetropes, low to moderate myopes, and high myopes. Methods: In this prospective study, the Eye Surface Profiler instrument was used to quantify anterior eye surface shapes of forty-five young adult participants (58 % females) aged between 18 and 35 years, including 15 emmetropes, 15 low to moderate myopes, and 15 high myopes. Sagittal height and axial radius of curvature of regions over the nasal and temporal corneal periphery and anterior sclera were exported and analysed. Results: After quality control of the data, 39 and 43 subjects had data analysed from the nasal and temporal sides, respectively. The nasal sides of the surfaces of the corneal periphery and anterior sclera had greater sagittal height in high myopes than in emmetropes across all regions (mean sagittal heights 2.44 ± 0.07 and 2.21 ± 0.04 mm, respectively, p = 0.02), but no significant differences were found between low to moderate myopes with emmetropes or with high myopes. No significant refractive group differences occurred for temporal anterior eye surface height. High myopes' nasal-temporal asymmetry of sagittal height was less than of emmetropes (means 0.20 ± 0.07 and 0.46 ± 0.06 mm, respectively, p = 0.02). High myopes also exhibited less nasal-temporal axial radius of curvature asymmetry than emmetropes (mean 0.35 ± 0.08 and 0.71 ± 0.08 mm, respectively, p = 0.01) across all regions. Conclusions: High myopes exhibited a different anterior eye surface shape than emmetropes, having greater sagittal height in the nasal corneal periphery and anterior sclera. There was less nasal-temporal asymmetry of sagittal height and axial radius of curvature in high myopes than in emmetropes. Asymmetric growth of the eye associated with myopia development may be the underlying reason. These findings have implications for design of contact lenses, particularly soft and larger rigid lenses such as mini-sclerals.